The Leadership Module Development Coaching based on Christian Insight - Manalu, Mei Lora Tri Oktavia; Wibawanta, Budi (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to develop a leadership coaching module based on Christian worldview that is feasible and effective in Lentera Harapan Medan School. The research design uses the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. However, this research does not cover the full cycle of the ADDIE process; its scope is limited to the Development stage, which involves creating training modules and evaluating their effectiveness in trials. Data collection methods included interviews, questionnaires, and tests. Interviews were conducted to validate learning design, content, and linguistic expertise. Questionnaires were distributed to teachers at Lentera Harapan Medan School, and a pilot test involved five teachers from various levels and backgrounds. The trial results show that the training effectively enhances teachers' understanding of implementing coaching leadership. The resulting training module from this research can serve as a reference for schools interested in implementing Coaching Leadership based on Christian worldview, fostering student potential discovery, and positively impacting teacher performance and school culture. The discussion within this research contributes to a deeper understanding of Coaching Leadership, particularly from a Christian perspective.